INTEGRATED APPROACH FOR DEFECT DETECTION IN CERAMIC TILES (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Quality control is an important issue in the ceramic tile industry. Price of ceramic tiles also depends on purity of texture, accuracy of color, shape etc. Considering this criteria, an integrated  defect detection and classification technique has been proposed which plays an important role in ceramic tiles industries to detect the defects and to control the quality of ceramic tiles.GLCM extracts the  texture features and these features  together with color features are used for analysis in classifiers such as SVM, KNN and Bayesian. Experimental results illustrated that  every classifier gives highest accuracy with HSV.